2015
DOI: 10.1080/15732479.2015.1086386
|View full text |Cite
|
Sign up to set email alerts
|

Punching shear capacity estimation of FRP-reinforced concrete slabs using a hybrid machine learning approach

Abstract: faculty of civil engineering, Institute of research and development, duy tan university, danang, Vietnam ABSTRACT Fibre-reinforced polymer (FRP) provides an alternative reinforcement for concrete flat slabs. This research proposes a hybrid machine learning model for predicting the ultimate punching shear capacity of FRPreinforced slabs. The model employs the least squares support vector machine (LS-SVM) to discover the mapping between the influencing factors and the slab punching capacity. Furthermore, the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…In this section of the article, to better evaluate the performance of the GPR model, the ANN [26] and LSSVM [9,27] are employed as benchmark methods. The reasons for selecting these two benchmark models are that ANN is widely accepted as an effective tool for nonlinear function approximation and this algorithm has been successfully employed for predicting concrete strength [10,13]; LSSVM is also an advanced machine learning method featured by high modeling accuracy [28][29][30][31] and it has been recently used for modeling concrete compressive strength [5].…”
Section: Results Comparisonmentioning
confidence: 99%
“…In this section of the article, to better evaluate the performance of the GPR model, the ANN [26] and LSSVM [9,27] are employed as benchmark methods. The reasons for selecting these two benchmark models are that ANN is widely accepted as an effective tool for nonlinear function approximation and this algorithm has been successfully employed for predicting concrete strength [10,13]; LSSVM is also an advanced machine learning method featured by high modeling accuracy [28][29][30][31] and it has been recently used for modeling concrete compressive strength [5].…”
Section: Results Comparisonmentioning
confidence: 99%
“…In addition to the SVMR-based models mentioned previously, several other global ML models have been successfully employed in the CE domain. Artificial neural networks (ANNs) have been employed to model the ultimate deformation capacity of RC rectangular flexure-critical columns (Inel, 2007) and to predict the shear strength of RC deep beams (Pal & Deswal, 2011) and the ultimate punching shear capacity of fiber-reinforced polymer (FRP)-reinforced slabs (Vu & Hoang, 2016). Random forests (RFs) have been utilized to predict building energy consumption (Ahmad, Mourshed, & Rezgui, 2017).…”
Section: Global ML Methodsmentioning
confidence: 99%
“…Comparative studies among some of these global ML techniques have been performed by many researchers (e.g., Ahmad et al, 2017;Pal & Deswal, 2011;Vu & Hoang, 2016). Ahmad et al (2017) carried out a performance comparison between ANNs and RFs for the prediction of building energy consumption; they found that both ANNs and RFs were comparable in terms of their predictive capabilities, with the ANN-based approach slightly outperforming the RF approach in terms of root mean squared error (RMSE).…”
Section: Global ML Methodsmentioning
confidence: 99%
See 2 more Smart Citations